2022
DOI: 10.1080/15476286.2022.2064073
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal tail of ribosomal protein Rps15 is engaged in cytoplasmic pre-40S maturation

Abstract: The small ribosomal subunit protein Rps15/uS19 is involved in early nucleolar ribosome biogenesis and subsequent nuclear export of pre-40S particles to the cytoplasm. In addition, the C-terminal tail of Rps15 was suggested to play a role in mature ribosomes, namely during translation elongation. Here, we show that Rps15 not only functions in nucleolar ribosome assembly but also in cytoplasmic pre-40S maturation, which is indicated by a strong genetic interaction between Rps15 and the 40S assembly factor Ltv1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The ribosome consists of various ribosomal proteins, including Rps15, which collaborate to translate RNA information into proteins. [24] The positioning and function of Rps15 within the ribosome are crucial for protein synthesis. Rps15 is located on the small subunit of the ribosome, where it interacts with ribosomal RNA and other ribosomal proteins, contributing to the structural composition of the ribosome.…”
Section: Discussionmentioning
confidence: 99%
“…The ribosome consists of various ribosomal proteins, including Rps15, which collaborate to translate RNA information into proteins. [24] The positioning and function of Rps15 within the ribosome are crucial for protein synthesis. Rps15 is located on the small subunit of the ribosome, where it interacts with ribosomal RNA and other ribosomal proteins, contributing to the structural composition of the ribosome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the C-terminal tail of RPS15 is thought to play a role in mature ribosomes, that is, in the process of translation elongation. [ 20 ] Recent studies have found that RPS15 not only plays a role in ribosome assembly, but also before cytoplasmic 40 seconds maturation. Changes in nucleoli (ribosome production site) have long been associated with cancer, and mutations in several RP are associated with an increased risk of cancer in human diseases.…”
Section: Discussionmentioning
confidence: 99%